Analisis Proses Pengelolaan Limbah Medis Padat pada Fasilitas Puskesmas di Kabupaten Lombok Barat - Nurma Firdaus; Ahlan Febrianto (Lembaga Publikasi Ilmiah Nusantara, 2025)
The management of solid medical waste in primary healthcare facilities is a crucial aspect of public health protection and environmental safety. This study aims to analyze the process of solid medical waste management at community health centers (Puskesmas) in West Lombok Regency, covering stages of segregation, collection, temporary storage, transportation, and final disposal. A qualitative descriptive method was employed through field observations, in-depth interviews with waste management officers, and a review of relevant policy documents. The findings indicate that most Puskesmas have implemented waste segregation according to categories; however, inconsistencies in practice were still observed. Temporary storage facilities generally did not meet technical standards, raising the risk of contamination. Waste transportation was carried out by third parties but often delayed due to limited fleets and high operational costs. Final disposal was conducted using centralized incinerators, yet limited capacity frequently caused delays and accumulation. From a human resources perspective, many staff members had not received specific training, resulting in suboptimal compliance with established procedures. In conclusion, solid medical waste management in West Lombok Puskesmas has been implemented but still faces challenges in technical, managerial, and regulatory aspects. Strengthening human resource capacity, providing standardized storage facilities, improving transportation and disposal systems, and enforcing strict supervision are necessary to ensure effective and compliant medical waste management.